Do Internal Control Activities Adversely Influence the Profitability and Solvency of South African SMMEs? - Bruwer, Juan-PierrÃ (Journal of Economics and Behavioral Studies, 2018)
Internal control activities should provide reasonable assurance surrounding the attainment of business objectives in the foreseeable future, be they financial or non-financial in nature. Recent studies suggest that internal control activities used within South African Small, Medium and Micro Enterprises (SMMEs) are inadequate and/or ineffective they do not provide reasonable assurance surrounding the attainment of relevant objectives. For this study emphasis was placed on whether internal control activities used by South African SMMEs had an adverse influence on their profitability and solvency. Data were obtained from 119 members of management of South African SMMEs, which allowed a total of14 relationships to be tested. Only four relationships were found to be statistically significant which led to the rejection of the two developed hypotheses. Stemming from the results, it appears that there may be a need for the development of formal policies pertaining to internal control within a South African SMME dispensation.